Vascular Epiphytic Diversity in a Neotropical Transition Zone Is Driven by Environmental and Structural Heterogeneity. (October 2019) - de la Rosa-Manzano, Edilia; Mendieta-Leiva, Glenda; Guerra-Pérez, Antonio; Aguilar-Dorantes, Karla María; Arellano-Méndez, Leonardo Uriel; Torres-Castillo, Jorge Ariel
Vascular epiphytes contribute significantly to tropical diversity. Research on the factors that determine vascular epiphytic diversity and composition in tropical areas is flourishing. However, these factors are entirely unknown in tropical-temperate transition zones, which represent the distribution limit of several epiphytic species. We assessed the degree to which climatic and structural variables determine the diversity of vascular epiphytic assemblages (VEAs) in a transition zone in Mexico: the El Cielo Biosphere Reserve. We found 12, 103 epiphytic individuals belonging to 30 species and 15 genera along a climatic gradient from 300 to 2, 000 m a.s.l. Bromeliaceae and Orchidaceae were the most species-rich families. Forests along the windward slope of the Sierra Madre Oriental (semideciduous forest and tropical montane cloud forest) had higher species richness than forests along the leeward slope (pine-oak forest and submontane scrub). Species richness was largely determined by seasonality and, to a lesser degree, by forest structure, whereas abundance was mainly determined by host tree size. Variation in VEAs composition was largely explained by climatic variables, whereas forest structure was not as important. VEAs differed among forest types and slopes in terms of taxonomic and functional composition. For example, certain bromeliad indicator species reflected differences between slopes. Although within-tree epiphytic species richness (alpha diversity) was low in this transition zone relative to other habitats, species turnover among forest types (beta diversity) was high. These findings suggest that each forest type makes a unique and important contribution to epiphytic diversity in this transition zone.